Purchasing power parity between Peru and China: analysis of trade and inflation (2002-2019) - Correa Lozada, Ana Cristhel (2025)
This research explores the application of the Purchasing Power Parity (PPP) theory in the context of trade between Peru and China during the period 2002-2019. The PPP, developed to investigate the link between exchange rates and market prices, remains relevant in a globalized environment where economies are interconnected. Trade between the two countries has grown exponentially, highlighting the need to understand how variations in inflation rates affect the nominal exchange rate (NER). Using an Error Correction Model (VECM), this study examines the validity of the PPP theory in this trade relationship, providing valuable insights for the formulation of economic policies and foreign trade strategies. This study confirms the long-term relationship between inflation and exchange rates, which is also influenced by structural factors and global events. These include external shocks, including global financial crises, which can distort the expected inflation-exchange rate relationship. The results are useful to assess the coherence of exchange rate adjustments with differences in inflation rates, which is crucial for designing effective economic policies and promoting lasting economic stability in the context of growing global interdependence.